2000
DOI: 10.1046/j.1365-8711.2000.03075.x
|View full text |Cite
|
Sign up to set email alerts
|

The extended rotation curve and the dark matter halo of M33

Abstract: We present the 21‐cm rotation curve of the nearby galaxy M33 out to a galactocentric distance of 16 kpc (13 disc scalelengths). The rotation curve keeps rising out to the last measured point and implies a dark halo mass ≳5×1010 M⊙. The stellar and gaseous discs provide virtually equal contributions to the galaxy gravitational potential at large galactocentric radii, but no obvious correlation is found between the radial distribution of dark matter and the distribution of stars or gas. Results of the best fit t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
366
2
11

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 372 publications
(404 citation statements)
references
References 31 publications
25
366
2
11
Order By: Relevance
“…This is also clear from the values of reduced-χ 2 . We therefore, conclude that the NFW model best represents these data, and this is consistent with the results of Corbelli and Salucci [16]. This is somewhat surprising for a late type, bulgeless galaxy like M33, since these late-type galaxies are often shown to have constant density cores (e.g., [10,11]).…”
Section: The Dark Halo Contributionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is also clear from the values of reduced-χ 2 . We therefore, conclude that the NFW model best represents these data, and this is consistent with the results of Corbelli and Salucci [16]. This is somewhat surprising for a late type, bulgeless galaxy like M33, since these late-type galaxies are often shown to have constant density cores (e.g., [10,11]).…”
Section: The Dark Halo Contributionsupporting
confidence: 89%
“…In this paper, we have chosen to model the HÁ rotation curve of M33 from Crobelli and Salucci [16]. Due to its proximity, M33 can be studied in exquisite detail, and it, therefore, provides a crucial testing ground of our ideas of galaxy formation.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its proximity, the rotation curve can be traced with unprecedented spatial resolution. M 33 is in fact one of the very few objects for which it has been possible to combine a high quality and high resolution extended rotation curve (Corbelli & Salucci 2000) with a well determined distance (assumed in this paper to be D = 840 kpc, Freedman et al 1991;Gieren et al 2013), and with an overwhelming quantity of data across the electromagnetic spectrum. Previous analyses have shown that the HI and CO velocity fields are very regular and cannot be explained by Newtonian dynamic without including a massive dark matter halo (Corbelli 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Then, for (6) and (7), M vir = η M 0 , with η ≃ 12 for (Ω 0 , Ω b ,z) = (0.3, 0.03, 3), and the limiting halo mass implies a lack of objects with ρ 0 > 4 × 10 −25 g/cm 3 and r 0 > 30 kpc, as is evident in Fig. 3.…”
Section: Halo Density Profilesmentioning
confidence: 71%
“…Then, although dark halo might extend down to the galaxy centers, it is only for r > r IBD that they give a non-negligible contribution to the circular velocity. b) DM is distributed in a different way with respect to any of the various baryonic components [16,6], and c) HI contribution to the circular velocity at r < r opt , is negligible [e.g. 17].…”
Section: Dark Matter Properties From the Universal Rotation Curvementioning
confidence: 99%